FY2019-FY2021 Medium-Term Budget. (Policy Papers; Policy Paper ;, 2018)
The FY 19 budget proposal is formulated against the backdrop of a strengthening global recovery and broadly balanced near term risks. The budget reflects a solid income position and a multi-year strategic agenda-operationalized in the Global Policy Agenda (GPA) and Board Work Program-to help members take advantage of the current cyclical upswing to bolster growth, harness the benefits of technology for all, while promoting resilience and responding swiftly to requests for program support. The net administrative budget for FY 19 remains unchanged in real terms, save for the extra customary travel allocation for Annual Meetings held abroad. This represents the seventh year in a row of flat real budget envelopes (excluding the 1\2 percentage point security related increase in FY 17). The proposal reflects reallocations of some 2 1\2 percent of the net budget. As the expected FY 18 outturn is just below the approved budget, carry-forward resources equivalent to 4 percent of the net budget from earlier years would still be available. Of these, roughly one half (USD 19 million) has been allocated upfront in the FY 19 budget process. The impact of savings and demands on the Fund's overall output structure is modest. Fund-financed structural resources are projected to shift slightly from global oversight towards multilateral surveillance as a net result of reallocations from completed to new policy work and reviews, in line with the Board Work Program. Fund-financed country work-bilateral surveillance, lending and capacity development-falls somewhat. Externally financed capacity development (CD) is expected to grow further. Support and governance areas continue to experience structural pressures. The same level of real resources is assumed over the medium-term. However, with medium-term risks to the economic outlook still on the downside, were upside spending pressures to emerge, the flat real budget stance would require a continued ability to find offsetting savings to meet emerging and unforeseen priorities. The capital budget envelope for FY 19 is broadly unchanged from the assumptions in the FY 18-20 Medium-Term Budget. The amounts for the outer years are indicative.